Comparative Study of Social Skills between Students Using Full Day and Regular Systems at SMK Negeri 2 Sungai Penuh - Desmiarni; Ambiyar; Mahesi Agni Zaus (AKADEMI TEKNIK ADI KARYA, 2024)
This study aims to determine the social skills of students who study in full-day majors and regular majors and to determine the differences in social skills between children who study in full-day majors and regular majors in SMK Negeri 2 Sungai Full. This type of research is quantitative research with experimental methods with the research subjects being regular class students and full day classes totaling 30 people used as samples of this study. Data analysis techniques test requirements analysis namely normality test, homogeneity test, and T-Test Independent. Based on the research data that has been obtained and explained, it can be concluded that there are differences in the social skills of students who study in the full-day Department Class and the regular Department Class of SMK Negeri 2 Sungai Full